Isolation of Escherichia coli 0157:H7 Strain from Fecal Samples of Zoo Animal. (30th December 2013) - Mohammed Hamzah, Aseel; Mohammed Hussein, Aseel; Mahmoud Khalef, Jenan
Abstract : The isolation and characterization of Escherichia coli O157:H7 strains from 22 out of 174 fecal samples from petting zoo animals representing twenty-two different species (camel, lion, goats, zebra, bear, baboon monkey, Siberian monkey, deer, elk, llama, pony, horses, fox, kangaroo, wolf, porcupine, chickens, tiger, ostrich, hyena, dogs, and wildcats) were investigated. One petting Al-Zawraa zoological society of Baghdad was investigated for E. coli O157:H7 over a 16-month period that spanned two summer and two autumn seasons. Variation in the occurrence of E. coli O157:H7-positive petting zoo animals was observed, with animals being culture positive only in the summer months but not in the spring, autumn, or winter. E. coli O157:H7 isolates were distinguished by agglutination with E. coli O157:H7 latex reagent (Oxoid), identified among the isolates, which showed that multiple E. coli strains were isolated from one petting zoo animal, in which a single animal simultaneously shed multiple E. coli strains; E. coli O157:H7 was isolated only by selective enrichment culture of 2 g of petting zoo animal feces. In contrast, strains other than O157:H7 were cultured from feces of petting zoo animals without enrichment.